Reduced statement credibility in interpreter-mediated interviews - Capus, Nadja; Hohl Zürcher, Franziska; Stoll, Mirjam (My University, 2023)
In this article, we examine whether the participation of an interpreter in police–suspect investigative interviews affects the perception of statement credibility based on the written record of the interview and, whether this relationship is influenced by the interaction style as depicted in the written record. This study thus addresses the question of whether the credibility problems observed in interpreter-mediated investigative interviews are carried forward to the case file and is based on the content analysis of 102 actual written records of police–suspect interviews conducted in Switzerland. Our results show, first, that written suspect statements are indeed considered to be less credible when an interpreter participates in the interview. Second, this effect is mediated by the questioning style and the fragmentation of discourse. According to the written records of interpreter-mediated interviews, interviewers use a more controlling questioning style and suspects provide shorter answers, which in turn results in reduced statement credibility.
Keywords: police investigative interview; interpreter; statement credibility; questioning style; fragmentation of discourse; written record